Internal Photoemission Spectroscopy Measurements of the Energy Barrier Heights between ALD SiO2 and Ta-Based Amorphous Metals. (19th June 2018) - Jenkins, Melanie A.; Klarr, Tyler; McGlone, John M.; Wager, John F.; Conley, John F.
Abstract : Internal photoemission spectroscopy is used to measure energy barrier heights in metal/insulator/metal (MIM) structures with plasma-enhanced atomic layer deposited SiO2 and amorphous metals TaWSi and TaNiSi and polycrystalline TaN bottom electrodes. With an Al top electrode, the TaWSi/SiO2 barrier height is 4.0 eV. Al and Au barrier heights with SiO2 were found to be 3.7 eV and 4.2-4.3 eV, respectively. With an Au top electrode, barrier heights between SiO2 and Ta-based bottom electrodes could not be reliably extracted. The Au top electrode device with a TaWSi bottom electrode exhibited switching behavior, pointing towards migration of a positively charged species in the dielectric which was not observed with the Al top electrode.